Effect of Admixtures on Durability Characteristics of Fly Ash Alkali-activated Material - Lukáš Procházka; Jana Boháčová (Emerging Science Journal, 2020)
This paper deals with the possibility of partial replacement of blast furnace slag with fly ash and fly ash after denitrification by SNCR method in alkali-activated materials based on granulated blast furnace slag. The aim of this paper is to verify the effect of fly ash on properties of alkali-activated materials based on blast furnace granulated slag. Frost resistance and resistance to aggressive environments, represented by demineralized water were tested. The reference mixture was based on blast furnace granulated slag activated by sodium water glass with silicate modulus of 2. Mixtures with an ash content of 10, 20, and 30% were then compared with the reference mixture. The influence of the denitrification process on fly ash and its use in mixed alkali activated materials was also compared. As a part of the experiment, alkali-activated pastes were also prepared. Infrared spectroscopy with Furier transformation was subsequently determined on these pastes. The reference mixture achieved the highest compressive strength in the experiment and the strength decreased with increasing amount of fly ash. In terms of flexural strength, the highest values were reached for mixtures with 10% slag replacement by fly ash. In the case of frost resistance, the significant increase of flexural strength, which was 50% for the reference mixture, is particularly interesting. For compressive strength, the frost resistance coefficient ranged from 0.95 to 1.00. In the case of resistance to aggressive environments, no differences were observed in the compressive strength, on the other hand, flexural strength decrease of up to 20% was detected for 10 and 20 percent replacement of slag with fly ash that did not undergo denitrification. Monitored properties did not show any negative effect of the denitrification process on fly ash properties. Infrared spectroscopy identified the main hydration product in the region of 945 cm-1which is a C-(A)-S-H gel and in combined mixtures with fly ash also N-A-S-H gel. Doi: 10.28991/esj-2020-01247 Full Text: PDF